Peningkatan Kemampuan Membaca Nyaring dengan Menggunakan Metode Latihan Siswa Kelas III SDN 5 Kayumalue Ngapa Kecamatan Palu Utara Sumriana (Mahasiswa Program Studi Magister Pendidikan Bahasa Indonesia Pascasarjana Universitas Tadulako - Sumriana, Sumriana (Bahasantodea, 2024)
The Problem of the research 1) How was the application of training methods to improve the ability of reading aloud of the third grade students of SDN 5 Kayumalue, Te researh aimed to describe the reading aloud ability through training methods of the third grade students of SDN 5 Kayumalue North Palu Subdistrict. This research was a classroom action research and the subjects of the research was the third grade students of SDN 5 Kayumalue North Palu Subdistrict. The research was conducted in two cycles, the research results showed that 1) the application of the training method in reading aloud learning the third grade students of SDN 5 Kayumalue North Palu based on the results of observation of student activity cycle I found unsatisfactory percentage (70%) and observation of the teacher activity (71.06%). In the second cycle, it has increased, the observation of the students have a satisfactory percentage (91.67%), while the results of the teachers activity observation were very satisfying (93.4%). 2) The result of applying the training method in reading aloud learning of the third grade students of SDN 5 Kayumalue, it could be seen from the results of the readong aloud test of the training methods in the first cycle was 72.60%. Based on students' acquisition value after the application of the training method in the first cycle was 16 students, there were 8 students who have achieved the criteria of succes (75) and 8 students who have not reached the Criteria of Succes. The factors causing cycle I, the students still found difficulty in reading aloud in aspects of pronunciation, intonation and pause. in the second cycle, there was a change in learning outcomes, the students who got score above the criteria of succes were 16 students with a success percentage of 91.15%. Therefore, this classroom action research showed that the application of the training method could improve the ability of reading aloud of the students. It was proved by more than 75% of the students could read aloud and achieved the criteria of succes (75).